A method for preparing VNxOy / V2O3 / PEDOT:PSS organic-inorganic flexible thermoelectric composite film

By using the molten salt method to prepare VNxOy/V2O3 nanoparticles in thermoelectric materials and combined with PEDOT:PSS, an organic and inorganic flexible thermoelectric composite film is formed, which solves the problem of existing thermoelectric materials lacking mechanical flexibility and low electron mobility, and realizes the problem of existing thermoelectric materials lacking mechanical flexibility and low electron mobility. Efficient thermoelectric conversion performance and wearable applications.

CN113948630BActive Publication Date: 2025-02-07CHANGSHU INSTITUTE OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111210789.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-18
Publication Date
2025-02-07
Estimated Expiration
2041-10-18

AI Technical Summary

Technical Problem

Existing thermoelectric materials lack mechanical flexibility and are difficult to achieve wearable applications of thermoelectric devices. At the same time, organic materials are relatively low in terms of electron mobility and power output.

Method used

VNxOy/V2O3 nanoparticles were prepared by molten salt method and combined with PEDOT:PSS to form an organic inorganic flexible thermoelectric composite film. This method creates a conductive channel at the interface between P-type V2O3 and PEDOT:PSS, and builds a built-in electric field with N-type VNxOy and P-type PEDOT to improve the conductivity and Seebeck coefficient of the thermoelectric composite film.

Benefits of technology

It has achieved efficient thermoelectric conversion performance. At 105 degrees Celsius, the Seebeck coefficient reaches 48.8μV/K, and the power factor reaches 1995.7μWm-1K-2. It has broad application prospects such as temperature differential power generation, thermoelectric refrigeration and wearable electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113948630B_ABST
    Figure CN113948630B_ABST
Patent Text Reader

Abstract

The present invention discloses a VN x O y / V2O3 nanoparticles and PEDOT:PSS organic-inorganic thermoelectric composite film method, using melamine and vanadium pentoxide as precursors to prepare VN x O y / V2O3 nanoparticles, VN x O y / V2O3 nanoparticle powder was mixed with PEDOT:PSS to prepare an organic-inorganic thermoelectric nanocomposite film with excellent thermoelectric performance, with a conductivity of 8278.4S / cm, a Seebeck coefficient of 48.8μV / K at 105 degrees Celsius, and a power factor of 1995.7μWm ‑1 K ‑2 .
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of thermoelectric materials, and more specifically relates to a VN x O y Preparation method of / V2O3 / PEDOT:PSS organic-inorganic flexible thermoelectric composite film. Background Art

[0002] With the rapid development of human economy and industrial society, humans are currently facing problems such as environmental pollution and energy shortage. Energy conservation and emission reduction are important means for us to protect the environment and save resources. Thermoelectric materials can directly convert electrical energy and thermal energy into each other using semiconductor materials, and collect waste heat energy in the environment. Thermoelectric nanocomposite films made of it do not require the use of any transmission parts, are noiseless and waste-free during operation, and do not pollute the environment. It is an environmentally friendly material with superior performance and broad application prospects.

[0003] The preparation process of thermoelectric materials greatly affects their thermoelectric performance. Therefore, while changing the formula, we must also strive to find better process conditions to prepare thermoelectric materials with superior performance. At present, the methods for preparing semiconductor thermoelectric materials are becoming more and more mature. The vapor phase growth method is suitable for preparing thin film materials, while the chemical method can not only prepare thin film materials, but also manufacture nanomaterials.

[0004] Polymer conductive inks have great value in the research of thermoelectric thin films. Poly(3,4-ethylenedioxythiophene):poly(styrene sulfonic acid), or PEDOT:PSS, is the most successful commercial polymer conductive ink. PEDOT:PSS is a p-type conductive polymer that can only achieve stable hole conduction.

[0005] Thermoelectric materials are a new energy material with very broad development prospects. Almost all temperature differences in nature and industrial waste heat can be used for thermoelectric power generation. It can utilize pollution-free energy existing in nature and has good comprehensive social benefits. To date, the most advanced thermoelectric materials are based on inorganic semiconductors, which provide high electron mobility but lack mechanical flexibility. In contrast, organic materials have sufficient flexibility but are low in electron mobility and power output. The present invention makes the thermoelectric material into an organic-inorganic flexible composite film, which can achieve the purpose of wearable thermoelectric devices. Summary of the invention

[0006] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a VN x O y / V2O3 / PEDOT:PSS organic-inorganic flexible thermoelectric composite film preparation method, the present invention uses the molten salt method to prepare VN x O y / V2O3 nanoparticles, and proposed a VN x O y The method of combining thermoelectric nanocomposite films with V2O3 nanoparticles and PEDOT:PSS. VN was prepared at high temperature using melamine and vanadium pentoxide as precursors by molten salt method. x O y / V2O3 nanoparticles, the interface between P-type V2O3 and PEDOT:PSS forms an interfacial conductive channel that is beneficial to carrier transport, thereby improving the conductivity of the organic-inorganic composite film; N-type VN x O y Built-in electric field enhancement with P-type PEDOT, and P-type PEDOT:PSS and P-type VN x O y The interface energy filtering effect of V2O3 nanoparticles improves the Seebeck coefficient of the thermoelectric composite film. x O y The thermoelectric composite film with a weight ratio of 70wt% of / V2O3 nanoparticles and PEDOT:PSS has a Seebeck coefficient of 48.8μV / K and a power factor of 1995.7μWm at 105 degrees Celsius. -1 K -2 The flexible thermoelectric composite film has broad application prospects, such as temperature difference power generation and thermoelectric refrigeration. It can also be used in wearable electronic devices. The composite film is placed close to human skin to generate electricity by the temperature difference between human body temperature and the outside world.

[0007] The present invention uses molten alkali salt as a catalyst to synthesize transition metal nitride TMNs under normal pressure. The main materials used in the present invention are melamine, V2O5, NaCl, KCl, and PEDOT:PSS. NaCl and KCl are low melting point additives used in the present invention. Molten salt can promote the growth of transition metal nitride TMNs by lowering the melting point of metal oxide precursors. The method can reduce the preparation of VN x O y / V2O3 nanoparticles synthesis temperature, improve VN x O y / V2O3 growth rate and shorten the synthesis time.

[0008] The present invention achieves the above-mentioned purpose through the following technical scheme: a VN x O y The method for preparing a V2O3 / PEDOT:PSS organic-inorganic flexible thermoelectric composite film comprises placing a mixture of V2O5, melamine, NaCl and KCl into a crucible, firing the sample at a high temperature in a CVD furnace (chemical vapor deposition furnace), and compounding the fired sample with PEDOT:PSS to finally prepare VN x Oy / V2O3 / PEDOT:PSS organic-inorganic flexible thermoelectric composite film.

[0009] The specific steps include:

[0010] a. Clean the quartz tube in the CVD furnace and a crucible of appropriate size with acetone, alcohol and deionized water by ultrasonic cleaning;

[0011] b. Put V2O5 and melamine in an agate mortar and grind them; then add NaCl and KCl to grind the sample;

[0012] c. Before placing the sample in the CVD, exhaust the air in the quartz tube with argon, then place the ground sample in step b into the crucible, and place the crucible into the high temperature zone of the CVD furnace;

[0013] d. After setting the temperature of the high temperature zone of the CVD furnace, press the start button to start firing the sample;

[0014] e. After the sample is fired, let the furnace cool down naturally to room temperature and get VN x O y / V2O3 nanoparticles; wherein x and y refer to the elements of N and O in 1 mol of V element, the range of x is 0.52-0.95, and y refers to the molar ratio of oxygen element, the range of y is 0.07-0.26;

[0015] f. VN x O y / V2O3 nanoparticles were placed in a beaker, and deionized water was added and centrifuged to remove the lower layer of solution; the upper layer of solution was centrifuged and measured for VN x O y / concentration of V2O3 nanoparticles aqueous solution;

[0016] g. Using a PVDF porous membrane as a substrate to assist the filtration of the PEDOT:PSS solution, dimethyl sulfoxide (DMSO) is added to the PEDOT:PSS solution; DMSO can be replaced by ethylene glycol, DMF or NMP solvent;

[0017] h. Prepare small test tubes, clean and dry them; add VN to each test tube. x O y / V2O3 aqueous solution, then add DMSO, dry the test tube with the aqueous solution, and then add the PEDOT:PSS solution treated in step g to obtain a mixed solution; calculated by the weight of the substance, VN x O y The weight percentage of / V2O3 and PEDOT:PSS is 1%-90%, and more preferably 70%.

[0018] i. Place the small test tube with the mixed liquid into an ultrasonic machine for ultrasonication to mix the mixed solution evenly.

[0019] g. Drop the prepared mixed solution onto the quartz glass substrate and let it stand to form a film.

[0020] k. Place the glass substrate in a CVD furnace, dry and anneal, and then drop a layer of DMSO on the film for surface modification, and then place it in a CVD furnace, dry and vacuum anneal to obtain VN x O y / V2O3 / PEDOT:PSS organic-inorganic flexible thermoelectric composite film.

[0021] Performance test: The electrode is made of silver paste. The electrode is led out with a lead wire, and the film is packaged to complete the preparation.

[0022] Preferably, in step a, the quartz tube is first rinsed with deionized water, and the water stains on the outer wall of the quartz tube are wiped dry with a clean towel, and then placed in a CVD furnace. A crucible with a length of 10 cm and a width of 3 cm is placed in a 500 ml beaker and ultrasonicated with acetone, alcohol, and deionized water for more than 3 times in sequence, and then placed in a dryer for drying. Then put it into the quartz tube, and then put the dried crucible into the central temperature zone of any temperature zone of the furnace. The temperature of the two temperature zones of the furnace is set at the same time: 20 degrees rise to 500 degrees in 30 minutes, keep warm for 30 minutes, rise to 1000 degrees in 30 minutes, keep warm for 30 minutes, end the program, and cool the CVD furnace naturally.

[0023] After the furnace cools down to room temperature, take out the crucible and observe whether there is white substance in the quartz tube. If so, clean the quartz tube again and burn the furnace clean according to the program set before.

[0024] Preferably, in step b, V2O5 and melamine are put into an agate mortar according to the ratio of element molar ratio N:V=1:2 and ground for about 2 hours; then NaCl and KCl are added according to the mass ratio of salt:mixture=20:1, wherein the molar ratio of the two salts Na:K=1:1; the sample is ground with a grinding rod for about 2 hours; this experiment requires a total of 5g of mixed sample, and a mask and rubber gloves need to be worn during the operation. V2O5 is a Class 2B carcinogen, which is harmful to the skin and respiratory tract. Be careful not to touch the skin directly during the operation. The mixed sample needs to be ground for about 4 to 5 hours. Grinding the sample finely can allow the sample to fully react during the chemical reaction.

[0025] Preferably, in step c, the sample is placed in a CVD furnace, and the sample is placed in the central temperature zone of the furnace high temperature zone with a slender iron rod. The quartz tube is evacuated for 20 minutes with a vacuum pump, and then the gas outlet is closed, and argon is passed into the CVD quartz tube, and the air pressure is returned to atmospheric pressure, and vacuumization is continued for 20 minutes, and this is repeated 3 times. Then the knob of the furnace gas outlet is tightened, the mechanical pump is closed, the pipe connected to the mechanical pump is unplugged, the knob of the furnace air inlet is opened, and argon is passed into the quartz tube, and when the pressure in the quartz tube is balanced with the outside world, the cock of the furnace gas outlet is unscrewed.

[0026] Preferably, in step d, the lid of the CVD furnace is closed and the temperature is set as follows:

[0027] The temperature in the high temperature zone is raised from room temperature to 110 degrees in 30 minutes, kept warm for 20 minutes, and then raised to 750 degrees at a heating rate of 2 degrees per minute, kept warm for 3 hours, and the furnace is allowed to naturally drop to room temperature.

[0028] Preferably, after the sample is burned in step e, after the temperature in the furnace drops to room temperature, the argon and mixed gas instruments are turned off and the sample is taken out of the furnace.

[0029] Preferably, in step f, the prepared VN x O y / V2O3 was put into a beaker, deionized water was added, ultrasonic centrifuged at 8000 rpm, repeated 6 times, and the lower layer solution was collected.

[0030] The lower layer solution was re-stirred, ultrasonicated, and centrifuged at 1000 rpm for 10 minutes. The upper layer solution was collected and its concentration was measured to be 12.2 mg / ml.

[0031] Preferably, in step g, PEDOT:PSS is filtered using a 450 nm syringe filter.

[0032] Preferably, the specific configuration method of step h is as follows:

[0033] Prepare a 1 mL test tube, clean and dry it. Add VN x O y / V2O3 aqueous solution, and then add DMSO. x O y / V2O3 aqueous solution was dried with deionized water, and then DMSO and PEDOT:PSS mixed solution were added to the dried test tubes, and ultrasonicated for 10 minutes; VN was controlled by calculating the weight of the substance. x O y / V2O3 nanoparticles and PEDOT:PSS weight percentage is 70%wt. It was found that VN x O yThe conductivity of the PEDOT:PSS thermoelectric composite film with a weight ratio of 70wt% of / V2O3 nanoparticles reached 8278.4S / cm. Figure 2 As shown in , the Seebeck coefficient reaches 20.22μV / K at 30℃ and 48.85μV / K at 105℃. Figure 3 As shown in the figure, the power factor reaches 338.46μWm at 30℃ and 105℃ respectively. -1 K -2 and 1995.71μWm -1 K -2 ,like Figure 4 as shown in .

[0034] Preferably, in step i, 120 microliters of the prepared solution is dropped onto a 1 cm×1 cm glass substrate and allowed to stand on a flat table, and the substrate is covered with a large cover to prevent dust in the air from floating on the substrate during the standing process and affecting the thermoelectric properties of the film. The sample is allowed to stand for 6 hours to make the final film uniform and smooth.

[0035] Preferably, in step j, the sample is placed in a CVD, argon is turned on, the gas flow rate is adjusted to 100 sccm, and the furnace is evacuated. The furnace temperature program is set to: rise to 90 degrees in 30 minutes, vacuum insulation for 6 hours, and dry annealing. After annealing, 6 microliters of DMSO is evenly dripped on the film for surface modification, and then placed in a CVD furnace, annealed in an argon environment at 140 degrees for 30 minutes, and the sample is taken out.

[0036] According to a second aspect of the present invention, the present invention provides a VN x O y / V2O3 / PEDOT:PSS thermoelectric composite film for the preparation of wearable thermoelectric devices.

[0037] The present invention realizes the synthesis of VN by molten salt method for the first time. x O y / V2O3, this method can greatly reduce costs; it also realizes a method for preparing thermoelectric materials based on a polymer mixture of PEDOT:PSS. The experimental method is simple, efficient, and low-cost. The prepared device is stable, which greatly expands the potential application of thermoelectric materials such as PEDOT:PSS. Compared with other methods, the present invention has significant differences and outstanding advantages:

[0038] 1. The salt in this method acts as a catalyst to promote VN x O y / V2O3 nanoparticles synthesis. The present invention can reduce VN x O y / V2O3 reaction temperature and synthesis time, argon was used as the protective gas to prevent the sample from being oxidized during the firing process.

[0039] 2. This method has low requirements for the overall preparation process equipment, which greatly reduces the cost of making flexible thermoelectric nanocomposite films.

[0040] 3. Thermoelectric composite membrane can directly convert thermal energy into electrical energy. The advantages of this composite membrane are as follows: small size, light weight, and no noise during operation; it will not cause any environmental pollution; it can recycle heat sources and convert them into electrical energy. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 The product characterization diagram of Example 1, wherein (a) is VN x O y / V2O3 nanoparticle crystal performance XRD curve, there are two crystal phases in the powder, one crystal phase matches the peak position of hexagonal V2O3 (PDF: No.34-0187), and the other crystal phase matches the peak position of cubic VN x O y (Between VN 0.52 O 0.26 PDF:No.34-1178 and VN 0.95 O 0.07 PDF:No.34-1179) peak position matching, Figure 1 (b) and (c) are VN x O y / V2O3 nanoparticles SEM image, nanoparticle size 50-200nm, nanoparticles aggregated into 1 micron wide, (d) VNxOy / V2O3 / PEDOT:PSS composite film thickness.

[0042] Figure 2 The conductivity variation trend of VNxOy / V2O3 nanoparticles and PEDOT:PSS composite films with different weight ratios with temperature.

[0043] Figure 3 The temperature variation trend of Seebeck coefficient of VNxOy / V2O3 nanoparticles and PEDOT:PSS composite films with different weight ratios.

[0044] Figure 4 The power factor variation trend of VNxOy / V2O3 nanoparticles and PEDOT:PSS composite films with different weight ratios with temperature.

[0045] Figure 5 The conductivity, Seebeck coefficient and power factor change trend with the increase of VNxOy / V2O3 nanoparticle weight ratio at temperature of 105 degrees. DETAILED DESCRIPTION

[0046] The PEDOT:PSS PH1000 required in the patent was purchased from Heraeus, V2O5, melamine, NaCl, and KCl were purchased from China National Pharmaceutical Group. The required chemical vapor deposition furnace (CVD) was purchased from Hefei Kejing Material Technology Co., Ltd., and the thermoelectric tester was purchased from Beijing Coreo Technology Co., Ltd.

[0047] Test method: The heating furnace heats the sample to the set test temperature. At the same time, the temperature difference heater in the bottom electrode starts to work. Through dynamic PID temperature control, the temperature difference between the upper and lower electrodes is stabilized at the set value. Two thermocouple probes measure the temperatures T1 and T2, and at the same time measure the potential difference dE between the two contact points to achieve the measurement of the Seebeck coefficient. Subsequently, forward and reverse currents pass between the upper and lower electrodes. The two thermocouple probes act as voltage probes to measure the voltage between the two contact points, achieving a four-terminal resistance test.

[0048] The specific steps include:

[0049] a. Clean the quartz tube and a crucible of appropriate size in the CVD furnace with acetone, alcohol and deionized water by ultrasonic cleaning; specifically, in step a, first rinse the quartz tube with deionized water, wipe the water stains on the outer wall of the quartz tube with a clean towel, and put it into the CVD furnace. Put a 10cm long and 3cm wide crucible into a 500ml beaker and ultrasonically clean it with acetone, alcohol and deionized water for more than 3 times, and then put it into the dryer for drying. Then put it into the quartz tube, and then put the dried crucible into the central temperature zone of any temperature zone of the furnace. Set the temperature of the two temperature zones of the furnace at the same time: 20 degrees for 30 minutes to 500 degrees, keep warm for 30 minutes, 30 minutes to 1000 degrees, keep warm for 30 minutes, end the program, and cool the CVD furnace naturally. After the furnace drops to room temperature, take out the crucible and observe whether there is white matter in the quartz tube. If there is, the quartz tube needs to be cleaned again, and then the furnace is burned clean according to the program set before the furnace.

[0050] b. Put V2O5 and melamine in an agate mortar and grind them; then add NaCl and KCl to grind the sample; specifically, in step b, put V2O5 and melamine in an agate mortar according to the element molar ratio N:V=1:2 and grind them for about 2 hours; then add NaCl and KCl according to the mass ratio of salt:mixture=20:1, where the molar ratio of the two salts Na:K=1:1; grind the sample with a grinding rod for about 2 hours; this experiment requires a total of 5g of mixed sample. The mixed sample needs to be ground for about 4 to 5 hours. Grinding the sample finely can allow the sample to fully react during the chemical reaction.

[0051] c. Before placing the sample in the CVD, use argon to exhaust the air in the quartz tube, then place the ground sample in the crucible, and place the crucible in the high temperature zone of the CVD furnace; specifically, in step c, place the sample in the CVD furnace, and use a slender iron rod to place the sample in the central temperature zone of the high temperature zone of the furnace. Use a vacuum pump to evacuate the quartz tube for 20 minutes, then close the air outlet, and then pass argon into the CVD quartz tube. When the air pressure returns to atmospheric pressure, continue to evacuate for 20 minutes, and repeat this process 3 times. Then tighten the knob of the furnace outlet, turn off the mechanical pump, unplug the pipe connected to the mechanical pump, open the knob of the furnace inlet, pass argon into the quartz tube, and when the pressure in the quartz tube is balanced with the outside world, unscrew the plug of the furnace outlet.

[0052] d. After setting the temperature of the high temperature zone of the CVD furnace, press the start button to start firing the sample; specifically, in step d, close the lid of the CVD furnace and set the temperature as follows: the temperature of the high temperature zone is increased from room temperature to 110 degrees within 30 minutes, kept warm for 20 minutes, and then increased to 750 degrees at a heating rate of 2 degrees per minute, kept warm for 3 hours, and the furnace is allowed to naturally drop to room temperature.

[0053] e. After the sample is fired, let the furnace cool down naturally to room temperature and get VN x O y / V2O3 nanoparticles; wherein x refers to the molar ratio of the N element, and the range of x is 0.52-0.95, and y refers to the molar ratio of the oxygen element, and the range of y is 0.07-0.26;

[0054] f. VN x O y / V2O3 nanoparticles were placed in a beaker, deionized water was added and centrifuged to remove the lower layer of solution. Stir and disperse again, centrifuge to remove the upper layer of solution, and measure VN x O y / concentration of V2O3 nanoparticles aqueous solution.

[0055] Specifically, in step f, the prepared VN x O y / V2O3 was placed in a beaker, deionized water was added, ultrasonic centrifuged at 8000 rpm, repeated 6 times, and the lower layer solution was collected. Part of the lower layer solution was dried and measured, and it was found that VN x O y / V2O3 nanoparticle crystal performance XRD curve Figure 1 As shown in (a), there are two crystal phases in the powder, one of which matches the peak position of the hexagonal phase V2O3 (PDF: No. 34-0187) and the other matches the peak position of the cubic phase VN x O y (Between VN 0.52 O 0.26PDF:No.34-1178 and VN 0.95 O 0.07 PDF:No.34-1179) peak position matching, Figure 1 (b) and (c) are VN x O y / V2O3 nanoparticles SEM image, nanoparticle size 50-200nm, nanoparticles aggregated into 1 micron wide, 10 micron long strips. The lower layer solution was re-stirred, ultrasonicated, centrifuged at 1000 rpm for 10 minutes, the upper layer solution was collected, and its concentration was measured to be 12.2 mg / ml.

[0056] g. Using a PVDF porous membrane as a substrate (450 nm syringe filter) to assist in filtering the PEDOT:PSS solution, dimethyl sulfoxide (DMSO) is added to the PEDOT:PSS solution; DMSO can be replaced by ethylene glycol, DMF or NMP solvent;

[0057] h. Prepare a 1ml test tube, clean and dry it. Add different volumes of VN to each test tube. x O y / V2O3 aqueous solution. Then add DMSO, dry the test tube with the aqueous solution, and then add PEDOT:PSS.

[0058] Specifically, prepare a 1 mL test tube, clean and dry it. Add 80.3 μL of VN x O y / V2O3 aqueous solution, and then add 10 microliters of DMSO. x O y / V2O3 aqueous solution was dried with deionized water, and then 10 μl of DMSO and 400 μl of PEDOT:PSS (VN x O y / V2O3 nanoparticles / PEDOT:PSS weight ratio 70%wt) and ultrasonicated for 10 min using an ultrasonic machine.

[0059] i. Place the small test tube with the mixed liquid in an ultrasonic machine for ultrasonication to mix the mixed solution evenly. Specifically, in step i, 120 microliters of the prepared solution is applied on a 1 cm 1 cm glass substrate, and allowed to stand on a flat table, and the substrate is covered with a large cover to prevent dust in the air from floating on the substrate during the standing process, which may affect the thermoelectric properties of the film. The sample is allowed to stand for 6 hours to make the final film uniform and smooth.

[0060] g. Drop the prepared mixed solution onto the quartz glass substrate and let it stand to form a film.

[0061] k. Place the glass substrate in a CVD furnace, dry and anneal, and after annealing, drop a layer of DMSO on the film for surface modification, then place it in a CVD furnace again, dry and vacuum anneal.

[0062] l. The electrodes are made of silver paste. The electrodes are led out with wires, and the film is packaged to complete the preparation.

[0063] Preferably, in step j, the sample is placed in a CVD, argon is turned on, the gas flow rate is adjusted to 100 sccm, and the furnace is evacuated. The furnace temperature program is set to: rise to 90 degrees in 30 minutes, vacuum insulation for 6 hours, and dry annealing. After annealing, 6 microliters of DMSO is evenly dripped on the film for surface modification, and then placed in a CVD furnace, annealed in an argon environment at 140 degrees for 30 minutes, and the sample is taken out.

[0064] Example 1-VN x O y / V2O3 nanoparticles and PEDOT:PSS (1% wt)

[0065] Steps ae are the same as the above steps ae.

[0066] f. The same as the preferred step F, mid-term VN x O y / V2O3 nanoparticle solution was diluted to 1.22 mg / ml.

[0067] g. Filter the PEDOT:PSS using a 450 nm syringe filter.

[0068] h. Prepare a 1 mL test tube, clean and dry it. Add VN x O y / V2O3 aqueous solution (1.22mg / ml), and then add 25 microliters of DMSO. Add 8.7 microliters of VN x O y The deionized water of the / V2O3 aqueous solution was dried, and then 25 μl of DMSO and 1000 μl of PEDOT:PSS (nanoparticle / PEDOT:PSS weight ratio 1%wt) were added to the dried test tubes, and ultrasonicated for 10 minutes.

[0069] Steps I and J are the same as steps I and J above.

[0070] It was found through measurement that VN x O y The conductivity of the PEDOT:PSS thermoelectric composite film with a weight ratio of 1wt% of / V2O3 nanoparticles reached 5369.3S / cm. Figure 2As shown in the figure, the Seebeck coefficient reaches 24.21μV / K at 30℃ and 26.08μV / K at 105℃. Figure 3 As shown in the figure, the power factor reaches 314.81μWm at 30℃ and 105℃ respectively. - 1 K -2 and 342.16μWm -1 K -2 ,like Figure 4 as shown in .

[0071] Example 2-VN x O y / V2O3 nanoparticles and PEDOT:PSS (5% wt)

[0072] Steps ae are the same as the above steps ae.

[0073] F. Same as the preferred step F, during which VN x O y / V2O3 nanoparticle solution was diluted to 1.22 mg / ml.

[0074] G. Filter the PEDOT:PSS using a 450 nm syringe filter.

[0075] H. Prepare a 1 mL test tube, clean and dry it. Add VN x O y / V2O3 aqueous solution (1.22mg / ml), and then add 25 microliters of DMSO. Add 45.3 microliters of VN x O y The deionized water of the / V2O3 aqueous solution was dried, and then 25 microliters of DMSO and 1000 microliters of PEDOT:PSS (nanoparticle / PEDOT:PSS weight ratio 5%wt) were added to the dried test tubes, and ultrasonicated for 10 minutes.

[0076] Steps I and J are the same as steps I and J above.

[0077] It was found through measurement that VN x O y The conductivity of the PEDOT:PSS thermoelectric composite film with a weight ratio of 5wt% of / V2O3 nanoparticles reached 7363.6S / cm. Figure 2 As shown in the figure, the Seebeck coefficient reaches 23.05μV / K at 30℃ and 24.95μV / K at 105℃. Figure 3 As shown in the figure, the power factor reaches 391.23μWm at 30℃ and 105℃ respectively. -1 K -2 and 418.5μWm -1 K -2 ,like Figure 4 as shown in .

[0078] Example 3-VN x O y / V2O3 nanoparticles and PEDOT:PSS (10% wt)

[0079] Steps ae are the same as the above steps ae.

[0080] F. Same as the preferred step F, during which VN x O y / V2O3 nanoparticle solution was diluted to 1.22 mg / ml.

[0081] G. Filter the PEDOT:PSS using a 450 nm syringe filter.

[0082] H. Prepare a 1 mL test tube, clean and dry it. Add VN x O y / V2O3 aqueous solution (1.22mg / ml), and then add 10 microliters of DMSO. Add 38.3 microliters of VN x O y The deionized water of the / V2O3 aqueous solution was dried, and then 10 microliters of DMSO and 400 microliters of PEDOT:PSS (nanoparticle / PEDOT:PSS weight ratio 10%wt) were added to the dried test tubes, and ultrasonicated for 10 minutes.

[0083] Steps I and J are the same as steps I and J above.

[0084] It was found through measurement that VN x O y The conductivity of the PEDOT:PSS thermoelectric composite film with a weight ratio of 10wt% of / V2O3 nanoparticles reached 8764.4S / cm. Figure 2 As shown in the figure, the Seebeck coefficient reaches 22.59μV / K at 30℃ and 24.61μV / K at 105℃. Figure 3 As shown in the figure, the power factor reaches 447.17μWm at 30℃ and 105℃ respectively. - 1 K -2 and 507.49μWm -1 K -2 ,like Figure 4 as shown in .

[0085] Example 4-VN x O y / V2O3 nanoparticles and PEDOT:PSS (30% wt)

[0086] Step ag is the same as the above-mentioned step ag.

[0087] H. Prepare a 1 mL test tube, clean and dry it. Add VN x O y / V2O3 aqueous solution (1.22mg / ml), and then add 10 microliters of DMSO. Add 14.8 microliters of VN x O y The deionized water of the / V2O3 aqueous solution was dried, and then 10 μl of DMSO and 400 μl of PEDOT:PSS (nanoparticle / PEDOT:PSS weight ratio 30%wt) were added to the dried test tubes, and ultrasonicated for 10 minutes.

[0088] Steps I and J are the same as steps I and J above.

[0089] It was found through measurement that VN x O y The conductivity of the PEDOT:PSS thermoelectric composite film with a weight ratio of 30wt% of / V2O3 nanoparticles reached 10260.5S / cm. Figure 2 As shown in , the Seebeck coefficient reaches 21.54 μV / K at 30°C and 23.96 μV / K at 105°C. Figure 3 As shown in the figure, the power factor reaches 476.06μWm at 30℃ and 105℃ respectively. -1 K -2 and 586.25μWm -1 K -2 ,like Figure 4 as shown in .

[0090] Example 5-VN x O y / V2O3 nanoparticles and PEDOT:PSS (60% wt)

[0091] Step ag is the same as the above-mentioned step ag.

[0092] H. Prepare a 1 mL test tube, clean and dry it. Add VN x O y / V2O3 aqueous solution (12.2mg / ml), and then add 10 microliters of DMSO. Add 51.6 microliters of VN x O yThe deionized water of the / V2O3 aqueous solution was dried, and then 10 microliters of DMSO and 400 microliters of PEDOT:PSS (nanoparticle / PEDOT:PSS weight ratio 60%wt) were added to the dried test tubes, and ultrasonicated for 10 minutes.

[0093] Steps I and J are the same as steps I and J above.

[0094] It was found through measurement that VN x O y The conductivity of the PEDOT:PSS thermoelectric composite film with a weight ratio of 60wt% of / V2O3 nanoparticles reached 13723.5S / cm. Figure 2 As shown in the figure, the Seebeck coefficient reaches 21.234μV / K at 30℃ and 23.118μV / K at 105℃. Figure 3 As shown in the figure, the power factor reaches 618.769μWm at 30℃ and 105℃ respectively. -1 K -2 and 693.317 μWm -1 K -2 ,like Figure 4 as shown in .

[0095] Example 6-VN x O y / V2O3 nanoparticles and PEDOT:PSS (80% wt)

[0096] Step ag is the same as the above-mentioned step ag.

[0097] H. Prepare a 1 mL test tube, clean and dry it. Add VN x O y / V2O3 aqueous solution (12.2mg / ml), and then add 10 microliters of DMSO. Add 137.7 microliters of VN x O y The deionized water of the / V2O3 aqueous solution was dried, and then 10 microliters of DMSO and 400 microliters of PEDOT:PSS (nanoparticle / PEDOT:PSS weight ratio 80%wt) were added to the dried test tubes, and ultrasonicated for 10 minutes.

[0098] Steps I and J are the same as steps I and J above.

[0099] It was found through measurement that VN x O y The conductivity of the PEDOT:PSS thermoelectric composite film with a weight ratio of 80wt% of / V2O3 nanoparticles reached 13565.9S / cm. Figure 2As shown in , the Seebeck coefficient reaches 18.082μV / K at 30℃ and 32.429μV / K at 105℃. Figure 3 As shown in the figure, the power factor reaches 443.547μWm at 30℃ and 105℃ respectively. -1 K -2 and 1362.905μWm -1 K -2 ,like Figure 4 as shown in .

[0100] Example 7-VN x O y / V2O3 nanoparticles and PEDOT:PSS (90%wt)

[0101] Step ag is the same as the above-mentioned step ag.

[0102] H. Prepare a 1 mL test tube, clean and dry it. Add VN x O y / V2O3 aqueous solution (12.2mg / ml), and then add 10 microliters of DMSO. Add 309.8 microliters of VN x O y The deionized water of the / V2O3 aqueous solution was dried, and then 10 microliters of DMSO and 400 microliters of PEDOT:PSS (nanoparticle / PEDOT:PSS weight ratio 90%wt) were added to the dried test tubes, and ultrasonicated for 10 minutes.

[0103] Steps I and J are the same as steps I and J above.

[0104] It was found through measurement that VN x O y The conductivity of the PEDOT:PSS thermoelectric composite film with a weight ratio of 90wt% of / V2O3 nanoparticles reached 12861.2S / cm. Figure 2 As shown in , the Seebeck coefficient reaches 18.411μV / K at 30℃ and 21.943μV / K at 105℃. Figure 3 As shown in the figure, the power factor reaches 435.95μWm at 30℃ and 105℃ respectively. -1 K -2 and 577.925μWm -1 K -2 ,like Figure 4 as shown in .

[0105] Example 8-VN x O y / V2O3 nanoparticles and PEDOT:PSS (0% wt)

[0106] The steps are the same as the preferred steps G, H, I, and J.

[0107] G. Filter the PEDOT:PSS using a 450 nm syringe filter.

[0108] H. The configuration method is as follows:

[0109] Prepare a 1 mL test tube, clean and dry it, add 20 μL DMSO and 400 μL PEDOT:PSS into the test tube, and sonicate for 10 min using an ultrasonic machine.

[0110] I. Take 120 microliters of the prepared solution and drop it on a 1cm×1cm glass substrate, and let it stand on a flat table. Cover the substrate with a large cover to prevent dust in the air from floating on the substrate during the standing process and affecting the thermoelectric properties of the film. Let the sample stand for 6 hours to make the final film uniform and smooth.

[0111] J. Place the sample in the CVD, turn on the argon gas, adjust the gas flow to 100 sccm, and evacuate the furnace. Set the furnace temperature program to: rise to 90 degrees in 30 minutes, keep in vacuum for 6 hours, dry and anneal. After annealing, evenly apply 6 microliters of DMSO on the film for surface modification, then place it in the CVD furnace, anneal at 140 degrees in an argon environment for 30 minutes, and take out the sample.

[0112] It was found through measurement that VN x O y The conductivity of the PEDOT:PSS thermoelectric composite film with a weight ratio of 90wt% of / V2O3 nanoparticles reached 4674.2S / cm. Figure 2 As shown in the figure, the Seebeck coefficient reaches 19.848 μV / K at 30°C and 23.238 μV / K at 105°C. Figure 3 As shown in the figure, the power factor reaches 184.138μWm at 30℃ and 105℃ respectively. -1 K -2 and 240.317 μWm -1 K -2 ,like Figure 4 as shown in .

[0113] By comparing the VN x O y / V2O3 nanoribbon weight ratio, it was found that VN x O yThe composite film of / V2O3 and PEDOT:PSS (weight ratio 70% wt) has the highest thermoelectric performance, with a conductivity of 8278.4S / cm, a Seebeck coefficient of 48.8μV / K at 105 degrees, and a power factor of 1995.7μWm -1 K -2 This is mainly due to VN x O y When the weight ratio of V2O3 nanoribbons is 70%wt, an interfacial conductive channel is formed at the interface of P-type V2O3 and PEDOT:PSS, which is conducive to carrier transport. The conductivity of the organic-inorganic composite film (70%wt) is increased to 8278 S / cm compared with the pure PEDOT:PSS organic film (conductivity ~4674S / cm). With the increase of V2O3 nanoribbons, the interfacial conductive channel gradually increases. However, the agglomeration effect of nanoparticles increases and a network structure appears. PEDOT and network VN x O y / V2O3 nanostrips will participate in the conduction at the same time, and the conductivity of the composite film will be enhanced. x O y When the weight ratio of / V2O3 nanoribbons reaches 60%wt, the conductivity reaches a maximum value of 13723S / cm. x O y The built-in electric field enhancement constructed with P-type PEDOT resulted in a decrease in conductivity, but it still reached 8278.4S / cm.

[0114] P-type PEDOT: PSS and P-type VN x O y / V2O3 nanostrips form an interface barrier for organic-inorganic composites. The interface barrier filters low-energy electrons and allows high-energy electrons to pass through. When the temperature is 30 degrees, VN x O y As the weight ratio of / V2O3 nanoribbons increases from 1%wt, the Seebeck coefficient shows a decreasing trend. This is mainly due to the increase in the weight ratio, the increase in the agglomeration effect of the nanoribbons, the weakening of the energy filtering effect of the nanoribbon and PEDOT interface, resulting in a gradual decrease in the Seebeck coefficient. The Seebeck coefficient of pure PEDOT:PSS organic film at 105 degrees is 23.238μV / K.

[0115] When the weight ratio reaches 70%wt, N-type VN x O y With the built-in electric field enhancement constructed with P-type PEDOT, the Seebeck coefficient is 48.8μV / K at 105 degrees, and the conductivity is also maintained at a high value. The power factor PF is the product of the conductivity and the square of the Seebeck coefficient, PF = σS 2 , the power factor reached 1995.7μWm -1 K-2 As the weight ratio continues to increase, a network structure gradually appears, the built-in electric field weakens, and the Seebeck coefficient decreases. When the weight ratio reaches 90%wt, the Seebeck coefficient is lower than that of pure PEDOT.

[0116] like Figure 5 As shown, when the temperature is 105 degrees, the conductivity, Seebeck coefficient, and power factor change with VN x O y / V2O3 nanoparticle weight ratio increases. In summary, when VN x O y / V2O3 / PEDOT:PSS (weight ratio 70% wt) composite film has the highest thermoelectric performance, with a power factor of 1995.7μWm at 105 degrees. -1 K -2 , the composite film has the best thermoelectric performance.

[0117] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A VN x O y / V2O3 / PEDOT:PSS organic-inorganic flexible thermoelectric composite film preparation method, V2O5, melamine, NaCl, KCl mixture is placed in a crucible, and the sample is fired at high temperature in a CVD furnace to obtain VN x O y / V2O3 nanoparticles; and the fired VN x O y / V2O3 nanoparticles were composited with PEDOT:PSS to prepare VN x O y / V2O3 / PEDOT:PSS organic-inorganic flexible thermoelectric composite film; Where x and y refer to the molar amounts of N and O in 1 mol of element V, x ranges from 0.52-0.95, and y ranges from 0.07-0.26; The specific steps include: a. Clean the quartz tube in the CVD furnace and a crucible of appropriate size with acetone, alcohol and deionized water by ultrasonic cleaning; b. Put V2O5 and melamine in an agate mortar and grind them; then add NaCl and KCl to grind the sample; c. Before placing the sample in the CVD, exhaust the air in the quartz tube with argon, then place the ground sample in step b into the crucible, and place the crucible into the high temperature zone of the CVD furnace; d. After setting the temperature of the high temperature zone of the CVD furnace, press the start button to start firing the sample; e. After the sample is fired, let the furnace cool down naturally to room temperature and get VN x O y / V2O3 nanoparticles; f. VN x O y / V2O3 nanoparticles were placed in a beaker, and deionized water was added and centrifuged to remove the lower layer of solution; the upper layer of solution was centrifuged and measured for VN x O y / concentration of V2O3 nanoparticles aqueous solution; g. Using a PVDF porous membrane as a substrate to assist in filtering the PEDOT:PSS solution, dimethyl sulfoxide is added to the PEDOT:PSS solution; DMSO can be replaced by ethylene glycol, DMF or NMP solvent; h. Prepare the test tube, clean and dry it; add VN into the test tube. x O y / V2O3 aqueous solution, then add DMSO, dry the test tube with the aqueous solution, and then add the PEDOT:PSS solution treated in step g to obtain a mixed solution; calculated by the weight of the substance, VN x O y / The weight percentage of V2O3 and PEDOT:PSS is 1%-90%; i. Place the test tube of the mixed liquid obtained in step h into an ultrasonic machine and mix the mixed solution evenly; g. Drop the mixed solution uniformly prepared by ultrasound onto a quartz glass substrate and let it stand to form a film; k. Place the glass substrate in a CVD furnace, dry and anneal, and then drop a layer of DMSO on the film for surface modification, and then place it in a CVD furnace, dry and vacuum anneal to obtain VN x O y / V2O3 / PEDOT:PSS organic-inorganic flexible thermoelectric composite film.

2. The method according to claim 1, characterized in that: In step a, first rinse the quartz tube with deionized water, wipe the water stains on the outer wall of the quartz tube with a clean towel, and put it into the CVD furnace; put a 10 cm long and 3 cm wide crucible into a 500 ml beaker and ultrasonically treat it with acetone, alcohol, and deionized water for more than 3 times, and then put it into a dryer for drying; then put it into the quartz tube, and then put the dried crucible into the central temperature zone of any temperature zone of the furnace; set the temperature of the two temperature zones of the furnace at the same time: 20 degrees for 30 minutes to 500 degrees, keep warm for 30 minutes, and then rise to 1000 degrees in 30 minutes, keep warm for 30 minutes, end the program, and cool the CVD furnace naturally; After the furnace cools down to room temperature, take out the crucible and observe whether there is white substance in the quartz tube. If so, clean the quartz tube again and burn the furnace clean according to the program set before.

3. The method according to claim 1, characterized in that: In step b, V2O5 and melamine are put into an agate mortar according to the element molar ratio N:V=1:2 and ground for 2 hours; then NaCl and KCl are added according to the mass ratio of salt:mixture=20:1, and the molar ratio of Na:K in the salt is calculated to be 1:

1.

4. The method according to claim 1, characterized in that: In step c, the sample is placed in a CVD furnace, and a thin iron rod is used to place the sample in the central temperature zone of the high temperature zone of the furnace; the quartz tube is evacuated with a vacuum pump for 20 minutes, and then the air outlet is closed, and argon gas is introduced into the CVD quartz tube, and the air pressure is returned to atmospheric pressure, and the evacuation is continued for 20 minutes, and this is repeated 3 times; then the knob of the furnace air outlet is tightened, the mechanical pump is turned off, the pipe connected to the mechanical pump is unplugged, the knob of the furnace air inlet is opened, and argon gas is introduced into the quartz tube, and when the pressure in the quartz tube is balanced with the outside, the plug of the furnace air outlet is unscrewed.

5. The method according to claim 1, characterized in that: In step d, close the lid of the CVD furnace and set the temperature as follows: The temperature in the high temperature zone is raised from room temperature to 110 degrees in 30 minutes, kept warm for 20 minutes, and then raised to 750 degrees at a heating rate of 2 degrees per minute, kept warm for 3 hours, and the furnace is allowed to naturally drop to room temperature.

6. The method according to claim 1, characterized in that: Step e: After the sample is fired, when the temperature in the furnace drops to room temperature, turn off the argon and mixed gas instruments and take the sample out of the furnace; In step f, the prepared VN x O y / V2O3 was placed in a beaker, deionized water was added, ultrasonicated and centrifuged at 8000 rpm, repeated 6 times, and the lower layer solution was collected; the lower layer solution was re-stirred, ultrasonicated, and centrifuged at 1000 rpm for 10 minutes, and the upper layer solution was collected, and its concentration was measured to be 12.2 mg / ml; In step g, the PEDOT:PSS was filtered using a 450 nm syringe filter.

7. The method according to claim 1, characterized in that: The specific configuration method of step h is as follows: Prepare a 1 mL test tube, clean and dry it, and add VN x O y / V2O3 aqueous solution, then add DMSO; VN x O y / V2O3 aqueous solution was dried with deionized water, and then DMSO and PEDOT:PSS mixed solution were added to the dried test tubes, and ultrasonicated for 10 minutes; VN was controlled by calculating the weight of the substance. x O y The weight percentage of / V2O3 nanoparticles and PEDOT:PSS is 70%wt.

8. The method according to claim 1, characterized in that: In step i, 120 μl of the prepared solution was dropped onto a 1 cm x 1 cm glass substrate and allowed to stand on a flat table; the sample was allowed to stand for 6 hours to make the final film uniform and smooth; In step j, the sample is placed in the CVD, the argon gas is turned on, the gas flow rate is adjusted to 100 sccm, and the furnace is evacuated; the furnace temperature program is set to: rise to 90 degrees in 30 minutes, vacuum insulation for 6 hours, drying and annealing; after annealing, 6 microliters of DMSO is evenly dripped on the film for surface modification, and then placed in the CVD furnace, annealed in an argon environment at 140 degrees for 30 minutes, and the sample is taken out.

9. A VN x O y / V2O3 / PEDOT:PSS thermoelectric composite film is used, characterized by: The VN x O y The / V2O3 / PEDOT:PSS thermoelectric composite film is prepared by any method described in claims 1-8 and is used to prepare a wearable thermoelectric device.

Citation Information

Patent Citations

  • Preparation method for thermoelectric composite material of polyaniline in-situ polymerization clad PEDOT modified nano-carbon

    CN105789423A

  • Production method of battery active material, battery active material, nonaqueous electrolyte battery and battery pack

    US20150129797A1